Solutions to increase the level of safety culture in Malaysian construction sites / Nurina Farhana Mohammad Zaki and Izatul Farrita Mohd Kamar - Mohammad Zaki, Nurina Farhana; Mohd Kamar, Izatul Farrita (2020)
An organization's safety culture is the product of personal and community beliefs, behaviors, expectations, and behavioral trends. The safety culture is implemented to identify areas that need to improve and raise awareness within the company. Moreover, due to high accident rates every year, fatality and incidence have forced the management to implement a safety culture at the construction site. The statistics by the Department of Safety and Health (DOSH) (2019), investigated by the State from January until June 2019 shows a higher number of occupational accidents from 2660 numbers occurred in 2018 to 3749 numbers in 2019. Thus, this study attempts to investigate the adoption level of safety culture in Malaysian construction sites. The objectives were to (1) identify the factors that influence the safety culture in Malaysian construction sites, (2) to determine the level of awareness for safety culture in Malaysian construction sites, and (3) to suggest solutions to increase the safety culture at Malaysian construction sites. Using the quantitative approach, a self-administered questionnaire was distributed to 155 targeted G7 Contractors in Klang Valley who are involved in Building Construction only. All the data collected were analysed using descriptive statistics. The study showed that the effectiveness of communication between employers and employees has increased the chances of workers to take proper action during critical situations. In terms of the level of awareness, most respondents perceived that the respondents are aware that organization and management give full commitment when it comes to safety at construction sites. In terms of the solutions, the majority of the respondents chose safety leadership is necessary to create workplace safety values. From the research, it can be concluded that the adoption of safety culture in terms of management and organization still has a long journey to travel to be accepted in the Malaysian construction industry.